THE SPIRITUALITIES:: THE FOUNDATIONS OF THE SCARY "INCLUSIVE DEMOCRACY" IN THE AMERICAS - Cardizi, Gabriella (Revista Gênero e Interdisciplinaridade, 2021)
The recognition of African participation and contribution in the history of humanity has been historically and constantly neglected by the hegemony of the discourses that outline the events and narratives about the achievements of civilized society. As a result, we see the permanence of subduing perspectives on this continent and its respective peoples, instead of their leading insertion in the more traditional topics of history teaching. In the first part of this training course, we were able to exemplify this realization by tracing the trajectory of the world’s population, its real original peoples, interests in shifting maps and where inspiration for myths of origin of monotheistic religions emerged. At this moment, with the advance of the centuries of human history, we can, in turn, demonstrate the same realization present both in the Industrial Revolution and in the struggles for the liberation of the colonies and the subsequent merit attributed to the American Revolution.